Failure mode and effect analysis in human islet isolation: from the theoretical to the practical risk. Issue 1 (4th March 2021) - Perrier, Quentin; Lavallard, Vanessa; Pernin, Nadine; Wassmer, Charles-Henri; Cottet-Dumoulin, David; Lebreton, Fanny; Bellofatto, Kevin; Andres, Axel; Berishvili, Ekaterine; Bosco, Domenico; Berney, Thierry; Parnaud, Géraldine
ABSTRACT: This study aimed to assess the global mapping risk of human islet isolation, using a failure mode and effect analysis (FMEA), and highlight the impact of quality assurance procedures on the risk level of criticality. Risks were scored using the risk priority number (RPN) scoring method. The risk level of criticality was made based on RPN and led to risk classification (low to critical). A raw risk analysis and a risk control analysis (with control means and quality assurance performance) were undertaken. The process of human islet isolation was divided into 11 steps, and 230 risks were identified. Analysis of the highest RPN of each of the 11 steps showed that the 4 highest risks were related to the pancreas digestion and islet purification stages. After implementation of reduction measures and controls, critical and severe risks were reduced by 3-fold and by 2-fold, respectively, so that 90% of risks could be considered as low to moderate. FMEA has proven to be a powerful approach for the identification of weaknesses in the islet isolation processes. The results demonstrated the importance of staff qualification and continuous training and supported the contribution of the quality assurance system to risk reduction.